Teachers’ Role in Managing Online Listening Class during Covid-19 Pandemic: An Investigation of Students’ Perception - Yosua Kuma Widjaja; Nurlaila Husain; Farid Muhamad (Universitas Negeri Gorontalo, 2022)
Teachers' roles are critical in the teaching and learning process for students. This study aims to determine students' perceptions of teachers' roles in managing online listening classes. The qualitative descriptive method was used to design this study. This research focused on 2018 English Department students who have completed their listening for academic purposes. Questionnaires and interviews were used to collect data. This study showed that teachers took on the following roles when teaching: controller, organizer, assessor, prompter, participant, resource, tutor, and observer. Teachers also got better at running online listening classes.